The abuse of Pastoral Authority in some churches in Nigeria today - Oyetade, Michael Oyebowale (NIU Journal of Humanities; Vol 3 No No. 2 (2018): KIU Journal of Humanities, Vol. 3 No. 2, June 2018, 2018)
This paper is a study of the role that spiritual leaders are to play in the lives of believers and the extent to which Christian religious leaders have abused authority invested into their hands over the years.  Authority which is a vital subject for churches today has also become controversial among Bible believers and churches have been torn apart. This old time deception has dogged the footsteps of the old time religion. The major findings were that: Religion or belief that should help man to deal with problems of human life that are significant, persistent, and intolerable has now become the sole problem man is having. Instead of finding fulfillment in the household of the faith, members become bound by fear, frustration, indoctrination, and manipulative mind control that have made their pursuit of God an endless drudgery punctuated by a driven and legalistic lifestyle. Churches should be sanctuaries not prisons. Faith should be the ultimate freedom not the ultimate trap. Throughout this paper, researcher discussed abuse of pastoral authority largely in the biblical context. Therefore, the abusive practices and principles we traced were limited to Christianity. Keywords: authority, abuse, church, pastoral authority, effect of abuse.